PRESERVAÇÃO DO MEIO AMBIENTE PARA UMA SOCIEDADE SUSTENTÁVEL - Souza, Diogo Fernandes de; Pereira, Letícia Elaine Lino; Martinelli, Renata Vallinhos; Biriba, Saulo Ramos; Pavanatti, Vanessa; Guimarães, Luciana Aparecida; Macena, Lincoln Villas Boas (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
... ver texto na íntegra.